Os hiperbens de Charles Taylor e a fundamentação transcendente da moral: as fontes do self e o teísmo - Silva, Maximino Gomes da (2010)
The object of this study is to analyze the possibility of transcendent moral reasoning trough the specific work Sources of the Self: The construction of modern identity from the Canadian philosopher Charles Taylor. The discussion about the notion of good or hyper good moral is fundamental on Taylor in order to understand the moral disarray according the main theories of morality in modernity. The plural and confusing field of current theories of morality requires the use of phenomenology and hermeneutics, which are the best possible languages for description and analysis of that reality. The proposed hypothesis in this work is that the whole rationale for the naturalistic moral that Taylor developed in this wor provides the basis to justify the defense of a transcendent moral in the religious sense, specifically the judeo-cristian tradition, which in their view does not diminish the dignity of human rationality and it can be a hermeneutical key for understanding the moral dilemmas in contempory society